2011
DOI: 10.1007/s10584-011-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of colonization and competition in forest landscape response to global climatic change

Abstract: The tree species composition of a forested landscape may respond to climate change through two primary successional mechanisms: (1) colonization of suitable habitats and (2) competitive dynamics of established species. In this study, we assessed the relative importance of competition and colonization in forest landscape response (as measured by the forest type composition change) to global climatic change. Specifically, we simulated shifts in forest composition within the Boundary Waters Canoe Area of northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Eventual overstory composition is the result of species level performance and competitive interactions at multiple early life stages (Pacala et al, 1996;Poorter, 2007). Notable recent studies have found indications that many tree species are not exhibiting northward expan-sions (Zhu et al, 2012) and have shown that other factors, such as competition, likely play a bigger role than climate variation (Clark et al, 2011;Xu et al, 2012). Decreasing growth by both temperate and boreal saplings as they approach their range limits suggests that temperature-mediated competitive dynamics are a key driver of sapling performance, forest composition, and range boundaries across the temperate-boreal transition zone.…”
Section: Discussionmentioning
confidence: 99%
“…Eventual overstory composition is the result of species level performance and competitive interactions at multiple early life stages (Pacala et al, 1996;Poorter, 2007). Notable recent studies have found indications that many tree species are not exhibiting northward expan-sions (Zhu et al, 2012) and have shown that other factors, such as competition, likely play a bigger role than climate variation (Clark et al, 2011;Xu et al, 2012). Decreasing growth by both temperate and boreal saplings as they approach their range limits suggests that temperature-mediated competitive dynamics are a key driver of sapling performance, forest composition, and range boundaries across the temperate-boreal transition zone.…”
Section: Discussionmentioning
confidence: 99%
“…), and (3) there is a diverse suite of extant tree species that allows for emergent behaviors, as expressed through changes in succession via competition, facilitation, release, and compensatory growth (Xu et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…(1) to contrast relative tree mortality rates and the extent of disturbance for four individual (single) disturbance regimes (fire, insects, wind, or forest management) vs. all four disturbance regimes operating concurrently (concurrent) under different climate change scenarios, and (2) to determine how climate change interacts with single and concurrent disturbance regimes to affect forest composition. We focused on a large landscape in north-central Minnesota (USA) because (1) all four disturbances are historically important, (2) climate change is expected to be substantial over the next century due to its relatively high latitude , and (3) there is a diverse suite of extant tree species that allows for emergent behaviors, as expressed through changes in succession via competition, facilitation, release, and compensatory growth (Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic landscape simulations have shown that forest disturbances can have major impacts on carbon storage and species composition under changing climatic conditions (Scheller and Mladenoff 2005). Disturbances provide many opportunities for colonization and establishment, and also affect the competitive balance between early‐ and late‐successional species at stand and landscape scales (Xu et al 2012). Accordingly, we hypothesized that periodic stand disturbances from forest harvesting would accelerate the rate at which forest types gain and lose area at the leading and trailing edges of their distributions, respectively.…”
mentioning
confidence: 99%